Essentials of medical pharmacology - Tripathi, K. D. (Jaypee Brothers Medical Publishers (P), Ltd., 2013)
New edition presenting latest developments in medical pharmacology. Includes therapeutic guidelines from WHO and BNF. Previous edition published in 2008.